Effects of surface roughness obtained by milling on interface bonding quality for 316H during metal additive forging - Xiuru Li; Boyang Luo; Jingyang Feng; Yong Zhao; Zhaocheng Wei; Jiang Guo; Minglong Guo; Minjie Wang (Journal of Materials Research and Technology)
The metallurgical bonding quality of bonded joints is affected by the substrate surface condition in metal additive forging process, and the surface roughness serves as a critical indicator for the surface condition. Nevertheless, the effect of surface roughness obtained by milling on interface bonding quality (IBQ) remains unclear, resulting in the lack of effective evaluation criteria for surface roughness in the milling process. This study prepared samples with various surface roughness through milling, and introduced three parameters, Ra, Rc, and Rsm, to quantify surface roughness. The interfacial morphology, elemental distribution, and mechanical properties were used to characterize the IBQ, and the influence of surface roughness on the IBQ was finally revealed. The results show that a reduction in surface roughness obtained by milling leads to an improvement in interfacial bonding, more uniform elemental distribution, and enhanced mechanical properties, all of which were related to the size of the initial voids and the dynamic recrystallization mechanism of the bonding interface. And the interface bonding process with various surface roughness involves grain boundary bulging and continuous dynamic recrystallization mechanisms. Finally, the Ra 1.2 μm was recommended as the evaluation criteria in milling process, and a high-feed face milling cutter equipped with wiper edge was suggested for machining to achieve high-quality and high-efficiency cutting of the substrate. This study provide a theoretical basis and practical guidance for the efficient acquisition of substrate surfaces suitable for interface bonding in metal additive forging process.